2020
DOI: 10.1186/s40246-019-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-analysis of whole blastocysts after trophectoderm biopsy indicated chromosome aneuploidy

Abstract: Background: To compare the concordance between trophectoderm (TE) analysis and whole blastocyst analysis of embryos from chromosomal structural rearrangement (SR) carriers. Method: Sixty-three abnormal blastocysts identified by preimplantation genetic testing for chromosomal structural rearrangement (PGT-SR) were included. The whole blastocysts were processed through multiple displacement amplification cycle and sequenced for 24-chromosome aneuploidy screening by next-generation sequencing (NGS). The sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In addition, 147 embryos were from patients who had an abnormal karyotype were used for analysis of positive controls. 36 2018 May 24 NGS Whole blastocyst NGS Tsuiko 37 2018 June 14 NGS ICM NGS Popovic 38 2018 July 58 NGS TE/ICM NGS Chuang 39 2018 December 29 NGS TE/ICM NGS Victor 16 2019 January 100 NGS TE/ICM NGS Victor 40 2019 February 8 NGS TE/ICM NGS Popovic 41 2019 April 45 NGS Blastocyst outgrowth NGS Lawrenz 42 2019 June 84 NGS TE/ICM NGS Huang 43 2019 July 50 NGS Whole blastocyst NGS Treff 44 2019 August 14 NGS TE SNP array Munne 45 2020 January 57 NGS TE NGS Ou 46 2020 January 63 NGS Whole blastocyst NGS Sachdev 47 2020 February 32 NGS TE/ICM NGS Girardi 9 2020 March 88 NGS TE/ICM NGS Navratil 48 2020 April 75 NGS TE/Whole blastocyst NGS Rubio 49 2020 May 64 NGS ICM NGS Lin 50 2020 June 41 NGS ICM NGS Abbreviations: aCGH, array comparative hybridization; CGH, comparative genomic hybridization; ICM, inner cell mass; NGS, next-generation sequencing; qPCR, quantitative real-time PCR; PGT-A, preimplantation genetic testing for aneuploidy; SNP, single nucleotide polymorphism; TE, trophectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 147 embryos were from patients who had an abnormal karyotype were used for analysis of positive controls. 36 2018 May 24 NGS Whole blastocyst NGS Tsuiko 37 2018 June 14 NGS ICM NGS Popovic 38 2018 July 58 NGS TE/ICM NGS Chuang 39 2018 December 29 NGS TE/ICM NGS Victor 16 2019 January 100 NGS TE/ICM NGS Victor 40 2019 February 8 NGS TE/ICM NGS Popovic 41 2019 April 45 NGS Blastocyst outgrowth NGS Lawrenz 42 2019 June 84 NGS TE/ICM NGS Huang 43 2019 July 50 NGS Whole blastocyst NGS Treff 44 2019 August 14 NGS TE SNP array Munne 45 2020 January 57 NGS TE NGS Ou 46 2020 January 63 NGS Whole blastocyst NGS Sachdev 47 2020 February 32 NGS TE/ICM NGS Girardi 9 2020 March 88 NGS TE/ICM NGS Navratil 48 2020 April 75 NGS TE/Whole blastocyst NGS Rubio 49 2020 May 64 NGS ICM NGS Lin 50 2020 June 41 NGS ICM NGS Abbreviations: aCGH, array comparative hybridization; CGH, comparative genomic hybridization; ICM, inner cell mass; NGS, next-generation sequencing; qPCR, quantitative real-time PCR; PGT-A, preimplantation genetic testing for aneuploidy; SNP, single nucleotide polymorphism; TE, trophectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have been conducted to analyze the concordance between niPGT-A and TE-biopsy PGT-A, or to compare the diagnostic efficiency between niPGT-A and TE-biopsy in ehivh the rest of the embryo or the whole embryo was regarded as the standard reference (13,19,(26)(27)(28). However, increasing evidence has demonstrated that the genetic results from TE biopsy, as well as the rest of the embryo mixed with ICM with TE, may not truly reflect the genetic status of the blastocyst-stage embryo due to mosaicism (9,13,29,30). A recommended, more reasonable way to verify the diagnostic efficiency of niPGT-A would be to compare BCM and multiple biopsy sites of the embryo, particularly the ICM samples (31).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported PGT-A results obtained using TE biopsy, but the concordance rate between TE and ICM karyotypes is approximately 62.1-86.2% [24][25][26]. Additionally, Ou et al re-examined embryos considered abnormal using PGT-SR and reported a concordance rate of 68% between TE biopsies and total blastocysts [27]. Another study conducted at our institution also found that the TE biopsy and total blastocysts had a chromosomal concordance rate of 67.7%.…”
Section: Discussionmentioning
confidence: 82%